Effect of temperature and relative humidity on the population dynamics of brinjal and tomato infesting whitefly, Bemisia tabaci (Jahangirnagar University Journal of Biological Sciences, 2019)
Abstract not availableJahangirnagar University J. Biol. Sci. 8(1): 83-86, 2019 (June)